Pengaruh Insentif Finansial, Motivasi, dan Stres Kerja terhadap Kepuasan Kerja Mitra Driver GoRide - Nina Desty Aspirariana Aksa; Ralina Transistari (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2021)
Abstract This study aims to analyze the effect of financial incentives, motivation, and job stress on the job satisfaction of GoRide drivers of PT Aplikasi Karya Anak Bangsa in Yogyakarta. The number of samples used in this study was 356 GoRide driver-partners, with the data collection method using a questionnaire measured by a Likert scale. The analytical method used is multiple linear regression analysis. The results showed that financial incentives and motivation positively affect the job satisfaction of GoRide drivers, while job stress does not affect the job satisfaction of GoRide drivers. The three independent variables can explain the effect of 42.7% on the job satisfaction variable, while the rest is explained by other variables not included in this study.